Study on the identification of protection priority areas in the Huaihe River Basin based on ecosystem services - Yan, Jun; He, Shihan; Yan, Shi; Yang, Xuemei; Wang, Xinying (Frontiers in Ecology and Evolution, 2025)
IntrudutionThe Huaihe River is the natural boundary between the north and the south of China. Its basin has important ecological service functions and plays an irreplaceable role in maintaining regional ecological balance and ensuring ecological security.MethodsBased on the land use data of Huaihe River Basin from 1990 to 2023, InVEST model, Local Moran’s I analysis, Spearman correlation coefficient and Marxan model were used to quantify the four ecosystem service functions of habitat quality, carbon storage, water yield and soil conservation.Results(1) From 1990 to 2023, the construction land and water in the study area increased by 5.1% and 0.5% respectively, and the cropland, forest, grassland and unused land decreased by 4.8%, 3.2%, 1.5% and 76.1% respectively. (2) Habitat quality, water yield and soil conservation showed a significant downward trend, which were 12.5%, 23.2% and 19.0%, respectively, showing a spatial distribution pattern of high in the south and low in the north. (3) The ecosystem services in the Huaihe River Basin form a high-high aggregation in the mountainous and hilly areas, and the aggregation in the plain areas is not significant, which generally reflects the synergy. (4) The core areas obtained under different protection target allocations of priority protection areas are basically similar, reflecting stability and continuity.DiscussionTherefore, it is necessary to protect the ecological environment according to local conditions, and finally achieve the goal of jointly improving ecosystem services and green development.